How to evaluate trade credit requests : a guide for bankers and the scorecard : a risk analysis tool (ITC GenevaCH, 1999)
Shows how to assess requests for trade credit from enterprises in developing and transition countries. Deals with basic lending facilities and practices involved in commercial transactions; and, practical aspects of assessing applications for trade credit by exporters and importers. Outlines ways in which trade credit transactions can be structured and monitored before and after disbursement.
Bibliography: p. 115-116